A MODERATION ANALYSIS: HOW DID FINANCIAL ATTITUDES INFLUENCE FINANCIAL MANAGEMENT BEHAVIOR OF SANTRI? - Bastomi, Mohamad; Nurhidayah, Nurhidayah (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
This study examined the financial management behaviors of Santri and Islamic students in Indonesia. It explores how financial attitudes impact financial management behavior by considering the moderating effects of Islamic financial literacy, financial well-being, and financial risk tolerance. The investigation employed a quantitative approach, surveying 335 Islamic boarding school students. The data analysis was conducted using the SEM-PLS method. The results show that financial attitudes, Islamic financial literacy, financial well-being, and financial risk tolerance have a significant effect on financial management behavior. Islamic financial literacy, financial well-being, and financial risk tolerance did not demonstrate a significant moderating effect on the relationship between financial attitudes and financial management behavior. This study offers valuable insights for practitioners, suggesting the development of financial education and training programs that emphasize cultivating positive financial attitudes.